Aftershock study and seismotectonic implications of the 8 March 2010 Kovancilar (Elazig, Turkey) earthquake (MW=6.1) - Tan, Onur; Pabuccu, Zumer; Tapirdamaz, M. Cengiz; Inan, Sedat; Ergintav, Semih; Eyidogan, Haluk; Kuluozturk, Fatih (Amer Geophysical Union, 2011)
A destructive earthquake (M-w = 6.1) occurred on the northeast end of the Palu segment of the East Anatolian Fault System (EAFS, eastern Turkey) on 8 March 2010. The spatial distribution of aftershocks suggests that the Palu segment does not terminate to the east of Palu town but extends in the N50 degrees E direction where it has produced a 30 km right stepover. Aftershock depths indicate a seismogenic brittle zone of about 15 km depth. The stress changes on the segments due to recorded events might have loaded more than 0.5 bars of stress on the NE end of the Palu segment and the SW end of the Goynuk segment. Therefore, a future earthquake on both segments may occur sooner than was expected before the occurrence of the Mw 6.1 earthquake on 8 March 2010. Citation: Tan, O., Z. Pabuccu, M. C. Tapirdamaz, S. Inan, S. Ergintav, H. Eyidogan, E. Aksoy, and F. Kuluozturk (2011), Aftershock study and seismotectonic implications of the 8 March 2010 Kovancilar (Elazig, Turkey) earthquake (M-W = 6.1), Geophys. Res. Lett., 38, L11304, doi:10.1029/2011GL047702.
Keywords: Eastern Turkey; 2003 Bingol; Fault